Hepatitis G virus infection in primary Sjögren's syndrome: analysis in a series of 100 patients. Issue 1 (1st January 1998) - Font, Josep; Tàssies, Dolors; García-Carrasco, Mario; Ramos-Casals, Manel; Cervera, Ricard; Reverter, Joan Carles; Sánchez-Tapias, José María; Mazzara, Roberto; Ingelmo, Miguel
Abstract : OBJECTIVE: To determine the prevalence and clinical significance of hepatitis G virus (HGV) infection in a large cohort of patients with primary Sjögren's syndrome (SS). PATIENTS AND METHODS: The study included 100 consecutive patients (92 female and eight male), with a mean age of 62 years (range 31–80) that were prospectively visited in our unit. All patients fulfilled the European Community criteria for SS and underwent a complete history, physical examination, as well as biochemical and immunological evaluation for liver disease. Two hundred volunteer blood donors were also studied. The presence of HGV-RNA was investigated in the serum of all patients and donors. Aditionally, HBsAg and antibodies to hepatitis C virus were determined. RESULTS: Four patients (4%) and six volunteer blood donors (3%) presented HGV-RNA sequences in serum. HGV infection was associated with biochemical signs of liver involvement in two (50%) patients. When compared with primary SS patients without HGV infection, no significant differences were found in terms of clinical or immunological features. HCV coinfection occurs in one (25%) of the four patients with HGV infection. CONCLUSION: The prevalence of HGV infection in patients with primary SS is low in the geographical area of the study and HCV coinfection is very uncommon. HGV infection alone does not seen to be an important cause of chronic liver injury in the patients with primary SS in this area.